Preliminary report of epiphytic and endophytic colonization of black oat (Avena strigosa) and wheat (Triticum aestivum) by Curtobacterium flaccumfaciens pv. flaccumfaciens in Brazil - Gonçalves, Ricardo Marcelo [UNESP]; Silva Júnior, Tadeu Antonio Fernandes da [UNESP]; Souza Filho, Ronaldo Caravieri [UNESP]; Maringoni, Antonio Carlos [UNESP] (My University, 2013)
Bacterial wilt, incited by Curtobacterium flaccumfaciens pv. flaccumfaciens (Cff), is one of the major bacterial diseases for dry bean in Brazil, with a higher incidence under no-tillage system after black oat (Avena strigosa) cultivation. There are also reports of wheat (Triticum aestivum) colonization by Cff under controlled conditions (Silva Júnior et al., 2012). In 2012, black oat and wheat plants grown in Ponta Grossa and Tibagi (Paranà state) were collected 90 days after sowing in crop fields with historic incidence of bacterial wilt of bean, and Cff was isolated in MSCFF culture medium (Maringoni et al., 2006), with specific methodologies to verify the natural epiphytic and endophytic colonization of grasses. Bacterial isolates with yellow and orange colonies, rod-shaped and Gram-positive were obtained, tested for pathogenicity on bean cv. Perola, and identified as Cff by PCR with the specific primers CffFOR2 and CffREV4. Bacterial isolates were pathogenic to bean. This is the first report of epiphytic and endophytic colonization of oat and wheat by Cff in Brazil, showing the importance of these grasses in the epidemiology of bean bacterial wilt in field conditions.